Honey can inhibit and eliminate biofilms produced by Pseudomonas aeruginosa - Lu, Jing (Sci Rep, 2019)
Chronic wound treatment is becoming increasingly difficult and costly, further exacerbated when wounds become infected. Bacterial biofilms cause most chronic wound infections and are notoriously resistant to antibiotic treatments. The need for new approaches to combat polymicrobial biofilms in chronic wounds combined with the growing antimicrobial resistance crisis means that honey is being revisited as a treatment option due to its broad-spectrum antimicrobial activity and low propensity for bacterial resistance. We assessed four well-characterised New Zealand honeys, quantified for their key antibacterial components, methylglyoxal, hydrogen peroxide and sugar, for their capacity to prevent and eradicate biofilms produced by the common wound pathogen Pseudomonas aeruginosa. We demonstrate that: (1) honey used at substantially lower concentrations compared to those found in honey-based wound dressings inhibited P. aeruginosa biofilm formation and significantly reduced established biofilms; (2) the anti-biofilm effect of honey was largely driven by its sugar component; (3) cells recovered from biofilms treated with sub-inhibitory honey concentrations had slightly increased tolerance to honey; and (4) honey used at clinically obtainable concentrations completely eradicated established P. aeruginosa biofilms. These results, together with their broad antimicrobial spectrum, demonstrate that manuka honey-based wound dressings are a promising treatment for infected chronic wounds, including those with P. aeruginosa biofilms.